2002
DOI: 10.1603/0046-225x-31.4.602
|View full text |Cite
|
Sign up to set email alerts
|

Chinese TortrixCydia trasias(Lepidoptera: Olethreutidae): Suppression on Street-Planting Trees by Mass Trapping with Sex Pheromone Traps

Abstract: Mass trapping to control the Chinese tortrix Cydia trasias (Meyrick) by removal of males using sex pheromone traps was evaluated in three plots of Chinese scholar-trees Sophora japonica L. in Beijing, China, in 2000. The traps, baited with 0.25 mg C. trasias synthetic sex pheromone (60% E8, E10-dodecadienyl acetate (E8, E10 Ð12:Ac) and 40% E8, E10-dodecadien-1-ol (E8, E10 Ð 12:OH), were deployed in the trapping plots at a density of one trap per two trees. The trees in all plots were planted Ϸ4.5 m apart along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The Cd entry through the Ca channel in the leaves results in the disturbing the plant-water relationship, which causing stomatal closure in many plants, leading to lower transpiration rate, and inhibition of photosynthesis due to the adverse effects on chlorophyll metabolism (Nazar et al 2012). Zhang et al (2002) determined that there was an increment in the concentrations of K, Fe, Zn, and Cu of wheat genotypes at the seedling stage, and a reduction in the concentrations of Ca and Mg. Furthermore, many researchers reported that excess Cd increased the concentration of Zn in shoot of tomato and goldenberry (Çikili et al 2016), rape and wheat genotypes (Zembala et al 2010), lettuce seedling (Xu et al 2015), and the Ca concentration in perennial ryegrass (Chen at al 2018).…”
Section: Netmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cd entry through the Ca channel in the leaves results in the disturbing the plant-water relationship, which causing stomatal closure in many plants, leading to lower transpiration rate, and inhibition of photosynthesis due to the adverse effects on chlorophyll metabolism (Nazar et al 2012). Zhang et al (2002) determined that there was an increment in the concentrations of K, Fe, Zn, and Cu of wheat genotypes at the seedling stage, and a reduction in the concentrations of Ca and Mg. Furthermore, many researchers reported that excess Cd increased the concentration of Zn in shoot of tomato and goldenberry (Çikili et al 2016), rape and wheat genotypes (Zembala et al 2010), lettuce seedling (Xu et al 2015), and the Ca concentration in perennial ryegrass (Chen at al 2018).…”
Section: Netmentioning
confidence: 99%
“…This strategy relies on species-specific synthetic chemical lures, such as sex and aggregation pheromones and food/host attractants, to attract insects to a trap where they would be confined and die (El-sayed et al 2006). Mass trapping has been used as an effective control method against a variety of pests such as the codling moth, Cydia pomonella L. (Madsen and Carty 1979), the goat moth, Coses coses L. (Faccioli et al 1993), the pink bollworm, Pectinophora gossypiella (Saunders) (Mafra Neto and Habib 1996), the Chinese tortrix, Cydia trasias (Meyrick) (Zhang et al 2002) and the leopard moth, Zeuzera pyrina Fab. (Hegazi et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Other recent studies with higher trap densities fare better. Zhang et al (2002) provide control of the Chinese tortrix Cydia trasias in urban street plantings of Chinese scholar‐trees when traps are deployed at densities equivalent to 110 ha −1 . Cork et al (2005) show that, in combination with other integrated pest management tactics, the control of a pyralid Leucinodes orbonali can be achieved using 100 traps ha −1 .…”
Section: Introductionmentioning
confidence: 99%
“…They are valuable tools for use in integrated pest management as they are non-toxic and do not represent a health risk to humans and animals. Indeed, the use of pheromones has been reported for a number of insect species, for such purposes as monitoring emergence patterns (Patricia et al, 2008), monitoring pest populations for management decisions (Kehat et al, 1992), assessing the levels of insecticide resistance in pest populations (Haynes et al, 1986(Haynes et al, , 1987, luring and trapping adult males to suppress pest populations (Zhang et al, 2002), and for mating disruption (Higbee et al, 2008;Il'Ichev et al, 2006;Stelinski et al, 2007).…”
Section: Introductionmentioning
confidence: 99%